2011
DOI: 10.1177/1558689811427912
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Mixing Methods in Quantitative Measurement Development, Validation, and Revision

Abstract: A framework for quantitative measurement development, validation, and revision that incorporates both qualitative and quantitative methods is introduced. It extends and adapts Adcock and Collier's work, and thus, facilitates understanding of quantitative measurement development, validation, and revision as an integrated and cyclical set of procedures best achieved through mixed methods research. It also offers a systematic guide concerning how these procedures may be undertaken through detailing key "stages," … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 36 publications
0
70
0
1
Order By: Relevance
“…As noted above, researchers should be prepared to evaluate evidence of an instrument's content as well as construct validity among the population in which it is to be disseminated. A mixed method approach, drawing upon the strengths of both qualitative and quantitative techniques, should ideally be adopted in order to do so (Luyt 2012b). In cross-cultural research, for example, the equivalence of measures should not be assumed.…”
Section: 'Doing Gender' Largely Reinforces Dominant Representations Cmentioning
confidence: 99%
“…As noted above, researchers should be prepared to evaluate evidence of an instrument's content as well as construct validity among the population in which it is to be disseminated. A mixed method approach, drawing upon the strengths of both qualitative and quantitative techniques, should ideally be adopted in order to do so (Luyt 2012b). In cross-cultural research, for example, the equivalence of measures should not be assumed.…”
Section: 'Doing Gender' Largely Reinforces Dominant Representations Cmentioning
confidence: 99%
“…[3][4][5] Two flexible frameworks for mixing qualitative and quantitative methods during development and validation have been proposed. 6,7 Despite this growing trend in mixed methods research, several authors have suggested more work is needed in determining appropriate and useful ways methods can be mixed to improve survey development, especially with regard to understanding the concept of validity in mixed methods research. 7,8 These broader methodological questions are of direct interest to the growing field of engineering education research where the mixing of quantitative and qualitative is a growing trend but mixed modes of validation have not been extensively explored.…”
Section: The Need For Mixed Methods Survey Validationmentioning
confidence: 99%
“…Therefore, validation is a dynamic, iterative process that must carefully consider context in addition to theory. 1,6,8,12,14 Messick (1995) acknowledged that all available evidence can and should be utilized when considering the validity of an assessment in a particular context, but also that certain evidence may be stronger than other types. 14 In particular evidence must be introduced to account for six particular aspects of the unified validity construct: content validity, substantive validity, structural validity, generalizability, external aspects of validity, and consequential validity.…”
Section: Mixed Methods Survey Validationmentioning
confidence: 99%
See 2 more Smart Citations